PARTISIPASI IBU RUMAH TANGGA DALAM PENGELOLAAN SAMPAH DOMESTIK TERHADAP PENCIPTAAN LINGKUNGAN YANG SEHAT - Mile, Rosi; -, Hermiaty (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
The purpose of this study: to determine the role of housewives in waste reduction towards the creation of a healthy environment. The method used is the method of survey and interview. The population is the number of residents in the district municipality Biringkanaya Makassar. A sample taken from the population. Sampling was conducted using simple random cluster sampling. Sample homogeneity lies in the social status of the respondents are women who are married and worked as a housewife. The primary data obtained through interviews, questionnaires and observations of the research location.The results showed that the age of respondents, the respondents' education, distance of residence of respondents with domestic waste disposal; consciousness waste bins, waste handling processes in the environment and the role of government respondents significantly affect the domestic waste management.Analysis was performed quantitatively using multiple linear regression to analyze the factors thought to influence the creation of a healthy environment. Data were analyzed using SPSS version 16.